Total synthetic efforts and structure elucidation in route to brocazine and cahuitamycin natural products - Fernando, Muthunaidelage Asantha Lloyd (Kansas State University, 2024)
Natural products continue to play a vital role in drug discovery. Work disclosed in this dissertation focusses on the asymmetric total synthetic efforts towards the brocazine family, with emphasis on E and F, as well as the structural elucidation of the cahuitamycin family, with emphasis on C. The brocazine family of natural products were isolated by Meng et al. in 2014 and 2016 from an endophytic fungus derived from the marine mangrove plant Avicennia marina named Penicillium brocae MA-231. Together, seven different brocazines (A-G) were isolated, and of those brocazine E showed the strongest activity against human pancreatic cancer cell line SW1990 (IC₅₀ of 2.1 μM), whereas brocazine F showed the strongest activity against lung cancer cell line NCI-H460 (IC₅₀ of 0.89 μM). Given the potent cytotoxicity of brocazines E and F, their intriguing polycyclic core structure, and structurally comparable natural products to brocazines isolated (i.e., rostratin A and penicibrocazine C), our laboratory is currently undertaking the development of a total synthesis route to access these natural products and their analogs. This work highlights the optimization of key steps (i.e., spirolactonization, diketopiperazine (DKP) formation, and sulfenylation) and the access of the brocazine E and F carbon framework in a reproducible manner. Cahuitamycin C was isolated from the marine microbe Streptomyces gandocaensis, which possesses Acinetobacter baumannii biofilm inhibitory activity (IC₅₀ = 14.5 μM). Our lab undertook synthetic efforts towards the total synthesis of cahuitamycin C, focusing on a convergent total synthesis route according to the literature precedence of accessing three key synthons. While working on the late stages of our route, a collaboration with the Wuest Group, who were focusing on cahuitamycin A, was established. Key structural differences between cahuitamycin A and C are the inclusion of a methyl group upon the arene within C. Together, the proposed isolated structures of both natural products were found to be incorrect, as established by synthetic efforts. Working together, another possible structural assignment was proposed. Unfortunately, this proposed structure was found to not be the correct structure. A third structure was proposed, involving an interesting biosynthetic transformation, but was also found to not be the structure of the natural product. Another structure has been proposed, at this stage by our lab alone, and efforts are being directed towards it currently. Fortunately, if this fourth proposed structure is also incorrect, the route will gain access to another class of natural products, oxachelin A and attinimicin.
Keywords: Total synthesis; Structure elucidation; Brocazine; Cahuitamycin; Diketopiperazine